IDENTIFICATION OF BIOACTIVE COMPOUNDS IN BUTTER AVOCADO PEEL EXTRACT (Persea americana) AS A POTENTIAL MEDICINAL RAW MATERIAL - Yugi Hari Chandra Purnama; Khumairoh Khaerani Huda (International Journal of Islamic and Complementary Medicine, 2025)
Indonesia is rich in biodiversity, including various plant species with potential medicinal properties. Onesuch plant is the avocado (Persea americana), whose peel—often discarded as waste—contains bioactivecompounds of pharmacological interest. This study aimed to identify the secondary metabolites present in the ethanol extract of Butter Avocado peel from Jember, Indonesia, through qualitative phytochemicalscreening. The research involved the preparation of simplicia, extraction using 96% ethanol via maceration, and phytochemical testing for four major compound groups: alkaloids, flavonoids, tannins, and saponins. The results showed positive reactions for all tested compounds, indicating the presence of these metabolites. Alkaloids were detected through precipitate formation with Dragendorff’s reagent, flavonoids through color change with HCl and magnesium powder, tannins via a color reaction with FeCl₃, and saponins through persistent foam formation after shaking in hot water. The results of this study indicated that avocado skin contained natural compounds that had the potential to serve as alternative raw materials in the development of traditional medicines and phytopharmaceuticals.   ABSTRAKIndonesia merupakan negara yang kaya akan keanekaragaman hayati, termasuk berbagai spesies tanaman yang berpotensi sebagai obat. Salah satu tanaman tersebut adalah alpukat (Persea americana), di mana bagian kulit buahnya yang sering dianggap limbah ternyata mengandung senyawa bioaktif dengan manfaat farmakologis. Penelitian ini bertujuan untuk mengidentifikasi senyawa metabolit sekunder yang terdapat dalam ekstrak etanol kulit buah alpukat varietas mentega asal Jember, Indonesia, melalui uji fitokimia secara kualitatif. Proses penelitian meliputi pembuatan simplisia, ekstraksi menggunakan etanol 96% dengan metode maserasi, serta uji fitokimia terhadap empat golongan senyawa, yaitu alkaloid, flavonoid, tanin, dan saponin. Hasil menunjukkan reaksi positif terhadap keempat senyawa tersebut. Alkaloid terdeteksi melalui pembentukan endapan dengan reagen Dragendorff, flavonoid melalui perubahan warna setelah penambahan HCl dan serbuk magnesium, tanin melalui perubahan warna setelah ditambahkan FeCl₃, dan saponin melalui pembentukan busa stabil setelah dikocok dengan air panas. Hasil penelitian ini menunjukkan bahwa kulit buah alpukat mengandung senyawa alami yang berpotensi sebagai sebagai bahan baku alternatif dalam pengembangan obat tradisional dan fitofarmaka.